Affect, emotion, and media audiences: the case of resilient reception. (November 2018) - Cavalcante, Andre
In this article, I place qualitative audience research in conversation with theories of affect. Informed by participant data from two qualitative audience studies I have conducted with lesbian, gay, bisexual, transgender, and queer (LGBTQ) audiences in the United States, I illustrate how cultural representations can make significant demands on one's emotional and affective life, requiring practices of rest, rebuilding, and reclamation. I call this process resilient reception, or the strategies audiences employ to manage the affectively turbulent power of media and communications technologies. I examine two examples of resilient reception that the participants in my studies practiced: orientation devices (how audiences oriented toward and away from media) and practices of immersion (how audiences immersed themselves in empowering interpersonal communities and media fare). Ultimately, I argue that theories of affect can complement ideological understandings of media audiences by offering a more embodied and dynamic optic.